Au cluster adsorption on perfect and defective MoS2 monolayers: structural and electronic properties. Issue 31 (25th July 2017) - Ju, Weiwei; Li, Tongwei; Su, Xiangying; Li, Haisheng; Li, Xiaohong; Ma, Dongwei
Abstract : The adsorption of Au n ( n = 1–4) clusters on perfect and defective MoS2 monolayers is studied using density functional theory. Abstract : The adsorption of Au n ( n = 1–4) clusters on perfect and defective MoS2 monolayers is studied using density functional theory. For the pristine MoS2 monolayer, our results show that the electrons are transferred from the support to the adsorbed Au clusters, thus a p-doping effect is achieved in the pristine MoS2 monolayer by the Au cluster adsorption, which is in good agreement with the experimental findings. The adsorption of Au clusters can introduce mid-gap states, which modify the electronic and magnetic properties of the systems. The adsorbates containing an odd number of Au atoms can introduce a spin magnetic moment of 1 μ B into the perfect MoS2 monolayer, while those systems containing an even number of Au atoms are spin-unpolarized. Two categories of defects, i.e., a single S vacancy and Mo antisite defect with one Mo atom replacing one S atom, are considered for the defective monolayer MoS2 . Compared with the pristine MoS2 monolayer, the adsorption energies for Au clusters are significantly increased for the MoS2 monolayer with a single S vacancy, and there are more electrons transferred from the MoS2 monolayer with an S vacancy to the Au clusters. The mid-gap states and odd–even oscillation magnetic behavior can also be observed when Au clusters are adsorbed on the MoS2 monolayer with an S vacancy. For those systems of Au clusters on MoS2 monolayers with Mo antisite defects, the adsorption energies as well as the magnitude and the direction of transferred charge are similar to those for the MoS2 monolayer with an S vacancy. The spin-polarizations appear in all systems with Mo antisite defects. Our investigations suggest that the electronic and magnetic properties of MoS2 nanosheets can be effectively modulated by the adsorption of Au clusters.